Do Patients Regret Having Received Systemic Treatment for Advanced Non‐Small Cell Lung Cancer: A Prospective Evaluation. (10th November 2020) - Hollen, Patricia J.; Gralla, Richard J.; Gentzler, Ryan D.; Hall, Richard D.; Coyne, Bethany; Cheng, Haiying; Halmos, Balazs; Gildersleeve, Jane; Calderon, Claudia; Hinton, Ivora; Weiss, Geoffrey; Crawford, Jeffrey; et al.
Abstract: Background: Thousands of patients annually receive treatment for advanced non‐small cell lung cancer (NSCLC), but little is known about their views on the decision to receive that treatment, or regret. This trial prospectively evaluated the incidence of regret and whether baseline characteristics, patient decision‐making parameters, or clinical progress early in the treatment course predicts regret. Materials and Methods: Patients receiving systemic treatment for advanced NSCLC completed every 3‐week patient reported outcome (PRO) assessment using the electronic Lung Cancer Symptom Scale (eLCSS‐QL), including the 3‐Item Global Index (3‐IGI; assessing overall distress, activities, and quality of life [QL]). A prespecified secondary aim was to determine the frequency of regret evaluated at 3 months after starting treatment. Patients were randomized to usual care or enhanced care (which included use of the DecisionKEYS decision aid). Results: Of 164 patients entered, 160 received treatment and 142 were evaluable for regret. In total, 11.5% of patients and 9% of their supporters expressed regret. Baseline characteristics did not predict regret; regret was rarely expressed by those who had a less than 20% decline or improvement in the 3‐IGI PRO score after two treatment cycles. In contrast, when asked if they would make the same decision again, only 1% not having a 20% 3‐IGI decline expressed regret, versus 14% with a 3‐IGI decline ( p = .01). Conclusion: The majority of patients having regret were identified early using the PRO 3‐IGI of the eLCSS‐QL measure. Identifying patients at risk for regret allows for interventions, including frank discussions of progress and goals early in the treatment course, which could address regret in patients and their supporters. Implications for Practice: This report documents prospectively, for the first time, the incidence of treatment‐related regret in patients with advanced lung cancer and outlines that risk of regret is associated with patient‐determined worsening health status early in the course of treatment. Identifying patients at risk for regret early in treatment (before the third cycle of treatment) appears to be crucial. Counseling at that time should include a discussion of consideration of treatment change and the reason for this change. Abstract : Considering that most patients are unlikely to have a major response treatment for advanced non‐small cell lung cancer, efforts should be made to avoid or reduce patient regret associated with treatment decision making. This article focuses on frequency of regret, prospectively evaluated in patients at 3 months after starting systemic treatment for advanced lung cancer.